1976
DOI: 10.1093/infdis/133.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance to Infection with Salmonella typhimurium in Mice

Abstract: Eight strains of inbred mice fell into two sharply defined groups. Four strains (CBA, A/JAX, C3H/He, and DBA/2) were resistant (LD50, greater than 10(5)) to Salmonella typhimurium C5 given subcutaneously. The other four strains (Balb/c, C57BL, B10.D2 [new line], and DBA/1) were susceptible (LD50, less than 10). No intermediate resistance was seen. Examination of the F1, F2, and parental backcross generations bred from matings of CBA and Balb/c mice showed that resistance behaved as a simple Mendelian dominant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(168 citation statements)
references
References 12 publications
4
163
0
1
Order By: Relevance
“…[25][26][27][28] It was recognized over 30 years ago that the susceptibility of inbred mice to infection with virulent Salmonella Typhimurium varied from strain to strain and that these differences were genetically controlled. 29,30 In general, classical inbred strains of mice can be classified into three distinct categories in regard to their susceptibility to Salmonella. 20,30 129S6/SvEvTac mice are extremely resistant to infection with Salmonella Typhimurium compared to A/J mice that present an intermediate susceptibility phenotype and show increased survival time with decreasing infectious dose but cannot survive the infection (Figure 2).…”
Section: Mouse Model Of Salmonella Typhimurium Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28] It was recognized over 30 years ago that the susceptibility of inbred mice to infection with virulent Salmonella Typhimurium varied from strain to strain and that these differences were genetically controlled. 29,30 In general, classical inbred strains of mice can be classified into three distinct categories in regard to their susceptibility to Salmonella. 20,30 129S6/SvEvTac mice are extremely resistant to infection with Salmonella Typhimurium compared to A/J mice that present an intermediate susceptibility phenotype and show increased survival time with decreasing infectious dose but cannot survive the infection (Figure 2).…”
Section: Mouse Model Of Salmonella Typhimurium Infectionmentioning
confidence: 99%
“…29 In this early paper, the authors showed that eight strains of inbred mice fell into two sharply defined groups with respect to resistance to infection. Four strains (CBA, A/J, C3H/He and DBA/2) were resistant (LD 50 410 5 ) to Salmonella Typhimurium C5 and the other four strains (BALB/c, C57BL, B10.D2 and DBA/1) were susceptible (LD 50 o10).…”
Section: Nramp1mentioning
confidence: 99%
See 1 more Smart Citation
“…The parental strains are known to differ in response to many pathogens. [26][27][28][29] The other notable advantage of this particular panel of RI strains is that both parental strains have been sequenced. 30 This makes it possible to use reverse genetic methods to test modifier genes.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Nramp1 is a major determinant of innate host resistance to infection. The gene affects intracellular replication of a wide range of pathogens including S. typhimurium, 37 Leishmania donovani, 38 M. lepraemurium, 39 M. intracellulare, 40 M. avium, 41 and the TB vaccine strain M. bovis -Bacillus Calmette-GuĂ©rin (BCG). 42 Specifically, a glycine-to-aspartic-acid change at amino acid 169 (G169D), located in the predicted transmembrane domain number 4 (TM 4), has removed the host's ability to inhibit pathogen growth.…”
Section: Discussionmentioning
confidence: 99%